Treatment efficacy and outcomes using a third generation shockwave lithotripter. (11th October 2013) - Neisius, Andreas; Wöllner, Jens; Thomas, Christian; Roos, Frederik C.; Brenner, Walburgis; Hampel, Christian; Preminger, Glenn M.; Thüroff, Joachim W.; Gillitzer, Rolf
<x xml:space="preserve">Abstract</x> Objectives To evaluate the clinical efficiency of a third generation electromagnetic shock wave lithotripter, the Lithoskop® (Siemens, Erlangen, Germany), regarding outcomes, stone disintegration, retreatment and complication rates. To compare the results of the Lithoskop with other currently available systems and the reference standard lithotripter, the HM‐3 (Dornier MedTech Europe GmbH, Wessling, Germany). Patients and Methods We analysed the data from 183 patients, including 13 children, undergoing extracorporeal shock wave lithotripsy (ESWL) for renal and ureteric calculi collected from a prospectively populated database. Outcomes were assessed by plain abdominal film of kidney, ureter and bladder and renal ultrasonography for radiopaque and computerized tomography for radiolucent stones 1 day after treatment and after 3 months. We analysed stone size and location before and after treatment, stone disintegration rate, retreatment rate, stone‐free and residual fragment rates after 3 months, along with auxiliary procedures and complications. Results The mean (range) patient age was 48.6 (1.3–81.4) years, including 13 children with a mean (range) age of 8.4 (1.3–16.7) years, and 77% of the patients were male. In all, 46% of the calculi were localized in the kidney and 54% in the ureter. Renal stones were localized in the upper, middle and lower calyx and in the renal pelvis in 9, 29, 30 and 32% of patients, respectively. Ureteric stones were localized in the upper, mid‐ and distal ureter in 29, 19 and 52% of patients, respectively. The median (range) stone size before ESWL was 10 (4–25) mm in the kidney and 8 (4–28) mm in the ureteric calculi. The overall stone‐free rate after 3 months was 91% (88% for renal and 93% for ureteric calculi); the mean number of sessions to achieve these rates was 1.3. Stone‐free rates and the required number of sessions were determined only by stone size. In 7.1% of the patients (n = 13) post‐interventional auxiliary procedures were necessary. We observed one perirenal haematoma as a major complication (0.5%), but this did not require any further therapy. Conclusions Clinical stone‐free rates with the Lithoskop are high and similar to those of other available systems, including the reference standard HM‐3 lithotripter. Retreatment and complication rates are low, supporting the use of ESWL as first‐line therapy for urinary calculi <10 mm, independent of stone location.